Benarkah Ahmadiyah sesat? : catatan bagi umat Islam Indonesia dalam menyikapi gerakan Ahmadiyah internasional - Mahally, Abdul Halim, 1971- (Jakarta : Cahaya Kirana Rajasa, 2005)
Controversion on Ahmadiyah as one of Islamic sects and misguided Islamic movements in Indonesia
Pustaka pilihan : p. 138-141
Keywords: Ahmadiyya; Ahmadiyya -- Indonesia